Depth‐ and Time‐Resolved Distributions of Snowmelt‐Driven Hillslope Subsurface Flow and Transport and Their Contributions to Surface Waters. Issue 11 (19th November 2019) - Tokunaga, Tetsu K.; Wan, Jiamin; Williams, Kenneth H.; Brown, Wendy; Henderson, Amanda; Kim, Yongman; Tran, Anh Phuong; Conrad, Mark E.; Bill, Markus; Carroll, Rosemary W.H.; Dong, Wenming; Xu, Zexuan; et al.
Abstract: Major components of hydrologic and elemental cycles reside underground, where their complex dynamics and linkages to surface waters are obscure. We delineated seasonal subsurface flow and transport dynamics along a hillslope in the Rocky Mountains (USA), where precipitation occurs primarily as winter snow and drainage discharges into the East River, a tributary of the Gunnison River. Hydraulic and geochemical measurements down to 10 m below ground surface supported application of transmissivity feedback of snowmelt to describe subsurface flow and transport through three zones: soil, weathering shale, and saturated fractured shale. Groundwater flow is predicted to depths of at least 176 m, although a shallower limit exists if hillslope‐scale hydraulic conductivities are higher than our local measurements. Snowmelt during the high snowpack water year 2017 sustained flow along the weathering zone and downslope within the soil, while negligible downslope flow occurred along the soil during the low snowpack water year 2018. We introduce subsurface concentration‐discharge ( C‐Q ) relations for explaining hillslope contributions to C‐Q observed in rivers and demonstrate their calculations based on transmissivity fluxes and measured pore water specific conductance and dissolved organic carbon. The specific conductance data show that major ions in the hillslope pore waters, primarily from the weathering and fractured shale, are about six times more concentrated than in the river, indicating hillslope solute loads are disproportionately high, while flow from this site and similar regions are relatively smaller. This methodology is applicable in different representative environments within snow‐dominated watersheds for linking their subsurface exports to surface waters. Key Points: Hillslope groundwater flow depth and water mass balance are reconciled using transmissivity feedback Solute concentrations are diminished during low snowpack years because of limited transmissive fluxes along the soil and weathering zones Subsurface concentration‐discharge relations were developed to explain time‐dependent hillslope exports of solutes to surface waters